Light Metals 2015 - Hyland, Margaret (The Minerals, Metals & Materials Series, 2016)
The Light Metals symposia are a key part of the TMS Annual Meeting & Exhibition, presenting the most recent developments, discoveries, and practices in primary aluminum science and technology. Publishing the proceedings from these important symposia, the Light Metals volume has become the definitive reference in the field of aluminum production and related light metal technologies. The 2015 collection includes papers from the following symposia: 1.Alumina and Bauxite 2.Aluminum Alloys: Fabrication, Characterization and Applications 3.Aluminum Processing 4.Aluminum Reduction Technology 5.Cast Shop for Aluminum Production 6.Electrode Technology for Aluminum Production 7.Strip Casting of Light Metals.